Primary care disease management for venous leg ulceration: study protocol for the Ulcus Cruris Care [UCC] randomized controlled trial (DRKS00026126) - Senft, Jonas; Fleischhauer, Thomas; Frasch, Jona; Rees, Wiebke van; Feißt, Manuel; Schwill, Simon; Müller-Christmann, Christine; Poß-Doering, Regina; Wensing, Michel; Müller-Bühl, Uwe; Szecsenyi, Joachim (Trials, 2022)
Venous leg ulcers (VLU) have a prevalence of 1-2% in developed countries, and affected patients are severely and long-term impaired in daily activities, work, and social participation. Evidence-based outpatient treatment based on compression therapy is frequently not implemented. The “Ulcus Cruris Care” project was established to develop a disease management concept to improve outpatient treatment for patients with VLU in German primary care. For this purpose, a multifaceted intervention was conceived consisting of an online training for general practitioners and medical assistants, standardized treatment recommendations, e-learning and print-based information for patients, and a software support for case management. The main aims of the Ulcus Cruris Care intervention are to promote standardized treatment according to current scientific knowledge, to facilitate case management for VLU patients exerted by medical assistants, and to support patient education and participation in the treatment process. The UCC trial was designed to evaluate the effectiveness of the Ulcus Cruris Care intervention.